Pemberdayaan siswa melalui penguatan kesiapan akademik, ketahanan mental, dan kompetensi multibahasa berbasis experiential learning - Maisarah, Maisarah; Iqbal, Muhammad; Ikhsan , Maulana; Tanjung, Aisyah Protonia; Wardani, Lusyana Eka; Wardhiah (PERDIKAN (Journal of Community Engagement), 2025)
Academic readiness, mental resilience, digital literacy, and multilingual competence are essential skills for students transitioning to higher education. Previous studies indicate that these students often experience academic adjustment challenges, psychological pressure, and limited exposure to foreign languages beyond Arabic and English. Although several programs have addressed academic guidance and mental health awareness, the integration of experiential learning within a comprehensive empowerment model for students remains limited. This program was developed based on the hypothesis that experiential, participatory engagement can significantly enhance students’ adaptive capacities. This community engagement initiative employed a Participatory Action Research (PAR) approach, involving 200 students from Madrasah Aliyah Dayah Terpadu Al-Muslimun in Aceh Utara. The program was implemented through four stages: preparation, socialization, implementation, and evaluation, using observation, interviews, structured tasks, and reflective discussions as data collection methods. Key outcome indicators included improved academic learning strategies, enhanced mental health awareness, increased digital literacy through the use of online journals, and basic competencies in Mandarin, Japanese, and French. The results demonstrated notable improvements in academic readiness, understanding of mental well-being, and learning motivation among third-year students. Second-year students demonstrated an increased ability to recognize basic vocabulary and showed a greater interest in foreign language learning. Overall, students' active participation and teachers' positive responses indicated the effectiveness of experiential learning in strengthening their adaptability. These findings align with empowerment theory, which posits that learners are active agents in their own personal development. No adverse effects were identified during program implementation. In conclusion, this empowerment program successfully enhanced students’ academic preparedness, mental resilience, and multilingual competence. Recommendations include establishing language interest classes, digital journal reading groups, and integrating mental health education into the curriculum.[Kesiapan akademik, ketahanan mental, literasi digital, dan kompetensi multibahasa merupakan kemampuan kunci bagi santri yang akan memasuki jenjang pendidikan tinggi. Berbagai studi menunjukkan bahwa remaja pesantren menghadapi tantangan adaptasi akademik, tingginya stres belajar, serta terbatasnya paparan bahasa asing selain Arab dan Inggris. Program-program terdahulu telah menyoroti pentingnya pembinaan akademik dan kesehatan mental, namun integrasi pendekatan experiential learning dalam penguatan multiaspek siswa pesantren masih terbatas. Kegiatan ini berangkat dari hipotesis bahwa model pemberdayaan berbasis pengalaman langsung dapat meningkatkan kemampuan adaptif siswa secara signifikan. Metode kegiatan menggunakan pendekatan Participatory Action Research (PAR) dengan melibatkan 200 siswa Madrasah Aliyah Dayah Terpadu Al-Muslimun Aceh Utara. Program dirancang melalui empat tahap persiapan, sosialisasi, pelaksanaan, dan evaluasi dengan teknik pengumpulan data melalui observasi, wawancara, tugas terstruktur, dan refleksi partisipatif. Indikator utama yang diukur meliputi peningkatan pemahaman strategi belajar, kesadaran kesehatan mental, kemampuan literasi digital melalui jurnal daring, serta kompetensi dasar bahasa Mandarin, Jepang, dan Perancis. Hasil menunjukkan adanya peningkatan kemampuan akademik, pemahaman konsep mental well-being, serta motivasi belajar pada kelompok siswa tingkat tiga. Pada kelompok tingkat dua, terjadi peningkatan kemampuan identifikasi kosakata dasar dan minat terhadap pembelajaran bahasa asing. Secara keseluruhan, partisipasi aktif siswa dan respons positif guru memperlihatkan efektivitas pendekatan experiential learning dalam memperkuat kapasitas adaptif santri. Hasil ini konsisten dengan teori pemberdayaan berbasis partisipasi yang menempatkan siswa sebagai aktor utama dalam proses pengembangan diri. Tidak ditemukan dampak negatif selama pelaksanaan program. Kesimpulannya, program pemberdayaan ini berhasil meningkatkan kesiapan akademik, ketahanan mental, serta kompetensi multibahasa siswa pesantren. Rekomendasi meliputi penguatan keberlanjutan melalui pembentukan kelas minat bahasa, kelompok baca jurnal digital, dan integrasi pelatihan kesehatan mental dalam kurikulum dayah.]